A Finite Element Method for Numerical Solution of Parabolic Di usion-Reaction Equation - Lima, Sadia Akter; Khondaker, Faizunnesa (GANIT: Journal of Bangladesh Mathematical Society, 2022)
This study considers the Finite Element Method (FEM), a well-conversant numerical method, used to evaluate approximate solutions of 2D higher-order non-homogeneous Di_usion-Reaction (DR) equation with more accuracy. In this paper, regular and irregular geometrical shapes are available for the FEM and this method is capable to provide more accurate solutions. Our present research also focuses on the acceptance of the FEM by utilizing absolute error analysis. This work includes two examples and their approximate results are portrayed both graphically and in a tabular form which is su_cient to ensure the validity and e_ciency of the FEM. GANIT J. Bangladesh Math. Soc. 42.2 (2022) 14- 23